Is Popularity Good for Plant Conservation? Impacts of “Plantito and Plantita CultureCulture” in Valencia City, Bukidnon, Philippines - Felice A. Beligolo; Dave P. Buenavista (Acta Natura et Scientia)
Commercial trading of plants is one of the most unregulated money-making industries in the world, especially in Asia. In the Philippines, many plant species, especially the endemics are already threatened of extinction. One of the threats faced by these species is the commercial trade of ornamental plants. Though prohibited under the wildlife resources conservation and protection laws, the trade persists due to their popularity in social media and local plant collectors. As such, this research aimed to quantitatively assess the illegal trade of ornamental plants in Valencia City, Bukidnon, Philippines. Specifically, it aimed to i) determine the socio-demographic profile of traders, ii) determine the species richness of the ornamental plants illegally traded, iii) determine the quantity of ornamental plant species illegally traded, iv) identify factors that drive the exploitation of the ornamental plants, and v) determine the distribution of the ornamental plants in different areas of Valencia City. The research adopted a covert research approach to monitor the plant trade activities in various street markets of Valencia City, Bukidnon. Observations and interviews have been discretely recorded using mobile phones and audio recorder to collect the data. The survey included both the wild species and cultivated ornamental plants. A total of 140 morphotypes (species, cultivars, hybrids, and varieties) belonging to 60 genera and 33 botanical families were recorded. A total of 1, 473 individual plants were recorded in five barangays of Valencia City. Aroids or arums of the Family Araceae were the most traded and collected ornamental plants with 10 genera and 48 morphotypes. This is followed by Acanthaceae (3 genera; 13 morphotypes), Asparagaceae (3 genera; 12 morphotypes), Commelinaceae (3 genera; 12 morphotypes), Euphorbiaceae (3 genera; 6 morphotypes), Orchidaceae (3 genera; 5 morphotypes) and Polypodiaceae (2 genera; 5 morphotypes).